The effect of value equity, brand equity, and relationship equity on repurchase intention - Fitri, Nurul Annisa; Yasri, Yasri (Universitas Negeri Padang, 2024)
The purpose of this study is to analyze the effect of value equity on repurchase intention, to analyze the effect of brand equity on repurchase intention, and to analyze the effect of relationship equity on repurchase intention. The population of this research is all consumers of Turkish Kebab Zahara Padang. Determination of the sample size is calculated using 10 multiplied by 19 indicators = 190 respondents. The sampling technique used was purposive sampling with the criteria of being a buyer of Kebab Turki Zahara Padang at least 3 times and being willing to be a respondent in the study. The data analysis technique used is multiple linear regression analysis. The results of the study show that value equity has a positive and significant effect on repurchase intention. Brand equity has a positive and significant effect on repurchase intention. Relationship equity has a positive and significant effect on repurchase intention. The correlation between value equity, brand equity, and relationship equity on repurchase intention is proven to be very strong, as evidenced by an R-value of 0.953.